Cognitive and conative functioning of judokas, shooters and volleyball players - Rado, I.; Zanini, D.; Drid, P. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The aim of this research is to show whether the uniformity of the cognitive and conative functioning in the heterogenic and complex sport space can also be noticed among different sports, not only within one. The study sample was indentical for both studies and included 11 judokas, 21 shooters, 12 volleyball player and 22 students. The constructs measured in this research rely on the cybernetic model of the cognitive and conative functioning. Those characteristics are assessed by applying the battery of tests of the cognitive efficiency and the conative functioning. The difference appeared for the variables AL-4, S-1 and ETA on the level of significance p<0.01, while for the variable DELTA the level of significance was p<0.05. The difference among the groups occurred for the variables NoEr4-11 on the level of significance p<0.01, while for the variables MinT2-41 and TB4-11 the difference is on the level of significance p<0.05. The serial and parallel processors do not favourize the athletes in comparison to the control group, which implies that the intellectual factor has a modelling effect on the success in sport, rather than the direct. It was confirmed that a dimension of emotional stability correlates to the sports competence in the strongest way. The athletes belonging to all three groups have a better coordination than non-athletes (even though it is not statistically significant for volleyball).